KEANEKARAGAMAN JAMUR BASIDIOMYCOTA DI HUTAN TROPIS DATARAN RENDAH SUMATERA, INDONESIA (Studi Kasus di Arboretum Fakultas Kehutanan Universitas Lancang Kuning Pekanbaru) - Wahyudi, Tri Roh; P, Sri Rahayu; Azwin, Azwin (Fakultas Kehutanan Universitas Lancang Kuning, 2016)
Tropical rain forest is one type of forest ecosystem that dominated most of Sumatra areal. Arboretum of Faculty of forestry, Lancang Kuning University is the one of tropical rain forest which the environment becomes a place or habitat for living things. This study aims to describe the various of fungi Basidiomycota. This study was going on May – June 2016. The making technique of data by exkplore an arboretum area to straight saw the fungi. The data collected were characteristic of fungi by morphology and detail pictue to indentification. The result shows that there are 25 species include in 12 families. Species that is Auricularia auricula, Schyzophylum commune, Ramariopsis kunzei, Agaricus crocopeplus, Lepiota sp, Lycoperdon Pyriforme, Crepidotus sp, Mycena incata, Mycena sp, Marasmieullus candidus, Marasmius andracaceus, Marasmius elegan, Marasmius sp1, Marasmius sp2, Collybia sp, Polyporus sp, Lignosus rhinocerus, Ganoderma aplanatum, Ganoderma sp, Fomitopsis cajanderi, Fomitopsis finicola, Grivola Frondosa, Grivola sp, Coltricia perennis dan Coltricia cinamomea. The number of fungi order were 5 (five) that could be Auriculateales, Aphylloporales, Agaricales, Polyporales and Hymenochaetales.